Ґенеза української дерев’яної церкви (витоки, принципи архітектурного формотворення, світовий контекст) - Шевцова, Галина Вікторівна (КНУБА, 2013)
Дисертація на здобуття наукового ступеня доктора архітектури за спеціальністю 18.00.01 – теорія архітектури, реставрація пам’яток архітектури. – Київський національний університет будівництва і архітектури МОН України, Київ, 2013. У дисертації наведено теоретичне узагальнення і нове вирішення наукової проблеми ґенези (витоки, етапи і принципи архітектурного формотворення) української дерев’яної церкви. Для вирішення проблеми застосовано сучасні теоретичні здобутки світових фахівців та оригінальні авторські підходи. Основною засадою дослідження є аналіз базових архітектурно-генетичних характеристик української дерев’яної церкви в контексті розвитку сакральної архітектури світу. Робота започатковує новий для вітчизняної науки напрям, що дозволить українськім фахівцям зосередити увагу на нерозроблених питаннях генеалогії вітчизняної і світової сакральної архітектури. Результати роботи науково обґрунтовують автентичність, самобутність, загальнонаціональний характер і виключне загальнокультурне значення архітектурного феномену української дерев’яної церкви, дозволяють якісно поліпшити рівень реставрації українських дерев’яних церков та їх авторського проектування в національних традиціях. Thesis on competition of a scientific degree of the doctor architecture on a specialty of 18.00.01 – theory of architecture, restoration of architectural monuments. – Kiev National University of Construction and Architecture of Ministry of Education and Science of Ukraine, Kiev, 2013. The thesis gives theoretical summary and new conclusion of Ukrainian wooden church genesis (sources, stages and principles of architectural formation) scientific problem. For the conclusion of the problem there were applied the modern international theoretical experience and author’s own original approaches. The investigation results are achieved by the analytic of Ukrainian wooden church’s main architecture-genetic characteristics. This analytic was fulfilled from the global position of worldwide sacral architecture developing review. The thesis is establishing a new for Ukrainian scientific tradition vector of researches that would help to concentrate researcher’s attention on some blind points of Ukrainian and worldwide sacral architecture genesis. The scientific results of the investigation prove the authentic, originality, national character and extreme world-cultural significance of Ukrainian wooden church’s architectural phenomena. Also they make possible to improve the quality of Ukrainian wooden churches restoration level and to push up the development of new Ukrainian wooden churches designing in national traditions.
Genesis of Ukrainian wooden church (sources, principles of architectural formation, worldwide contest)
Keywords: українська дерев’яна церква; ґенеза; витоки; принципи архітектурного формотворення; світовий контекст; архітектурно-генетичні характеристики; автентичність; самобутність; загальнонаціональний характер; загальнокультурне значення; Ukrainian wooden church; genesis; sources; principles of architectural formation; worldwide contest; architecture-genetic characteristics; authentic; originality; national character; world-cultural significance